Use of Wittig reaction for the synthesis of conjugated Aza-BODIPYs and their spectral and electrochemical properties. Issue 11 (16th March 2017) - Koch, Angira; Kumar, Sunit; Ravikanth, Mangalampalli
Abstract: The 2-formyl 1, 3, 5, 7-tetraaryl aza-BODIPY and 2-formyl-6-bromo 1, 3, 5, 7-tetraaryl aza-BODIPY were subjected to Wittig reaction with three different ylides under simple reaction conditions and afforded the conjugated aza-BODIPYs in high yields. The aza-BODIPYconjugates resulted from 2-formyl-6-bromo aza-BODIPYs were reacted further with 4-anisyl boronic acid under mild Pd(0) coupling conditions and afforded 1, 2, 3, 5, 7-pentaaryl aza-BODIPYconjugates. The method works efficiently and allows to introduce different substituents at the aza-BODIPY core. All compounds were characterized by HRMS, 1D, 2D NMR, absorption, fluorescence and electrochemical techniques. The spectral and electrochemical studies indicated that the introduction of conjugated substituents at the aza-BODIPY core alter the electronic properties significantly. Graphical abstract: The formyl aza-BODIPYs were subjected to Wittig reaction to prepare conjugated aza-BODIPY dyes.